Religious Education in Indonesia: Between Tolerance and Ideological Contestation - Fitriani, Mohamad Iwan; Nazar Naamy (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2024)
This study focuses on how religious education contributes to build tolerance behavior and prevent or minimize ideological contestation. Therefore, this study answers a research question, namely; What are the relevant models of religious education to promote  religious tolerance?. Using a qualitative approach, data were collected through documentation and interviews with informants from several selected schools and madrasas in West Lombok-West Nusa Tenggara. Data collection was also strengthened with Focus Group Discussion. Then, the data analysis used was a thematic analysis. The study found that; The relevant model of religious education to build ideal tolerance is a model of religious education characterized by components (goals, teachers, content and methods) support inclusive values and behaviors. Without inclusivism in each of these components, religious education will lead to ideological contestation, a contest of truth based on the ideology believed by each adherent of a certain belief or religion.